2010
DOI: 10.1155/2010/657039
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix Metalloproteases and Endothelin‐1 in Infection‐Associated Preterm Birth

Abstract: Preterm birth (PTB) is clinically defined as any delivery which occurs before the completion of 37 weeks of gestation, and is currently the most important problem in obstetrics. In the United States, PTB accounts for 12-13% of all live births, and, with the exception of fetuses suffering from anomalies, is the primary cause of perinatal mortality. While the risk factors for PTB are numerous, the single most common cause is intrauterine infection. As there is currently no FDA-approved therapy for infection-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Pro-inflammatory cytokines interact with each other as well as with PGs in a feed-forward cascade, hence amplifying the inflammatory response ( 6 , 7 ). Furthermore, pro-inflammatory cytokines enhance the expression of matrix metalloproteinase (MMPs), which are zinc-dependent enzymes that catalyze the degradation of collagen constituted-extracellular matrix of the cervix, fetal membrane, placenta, and uterus ( 8 11 ). Elevated levels of MMP-9 in the maternal plasma, and MMP-3 and MMP-8 in the amniotic fluid are associated with preterm labor (PTL) and/or microbial invasion of the amniotic cavity ( 11 13 ).…”
Section: Mechanism Of Inflammation and Infection-associated Preterm Lmentioning
confidence: 99%
“…Pro-inflammatory cytokines interact with each other as well as with PGs in a feed-forward cascade, hence amplifying the inflammatory response ( 6 , 7 ). Furthermore, pro-inflammatory cytokines enhance the expression of matrix metalloproteinase (MMPs), which are zinc-dependent enzymes that catalyze the degradation of collagen constituted-extracellular matrix of the cervix, fetal membrane, placenta, and uterus ( 8 11 ). Elevated levels of MMP-9 in the maternal plasma, and MMP-3 and MMP-8 in the amniotic fluid are associated with preterm labor (PTL) and/or microbial invasion of the amniotic cavity ( 11 13 ).…”
Section: Mechanism Of Inflammation and Infection-associated Preterm Lmentioning
confidence: 99%
“…Although we have previously reported that preventing the action of ET-1 (17), as well of MMPs (30), controls preterm birth individually, the data presented here are the first to show that ET-1 leads to production of MMPs in stimulated gestational tissue just as it does in injured myocardium and other pathologic settings (31). Although the role of endothelin in cardiovascular and other diseases has been investigated, its function in reproductive disorders is not as well understood.…”
Section: O V E M B E R -D E C E M B E R 2 0 1 0 C O N T R O L O F P Rmentioning
confidence: 51%
“…Histopathological studies demonstrate that PROM is frequently preceded by infection and inflammation of the intra-amniotic cavity and the fetal membranes. Moreover, these inflammatory changes are usually observed near the reported site of membrane rupture (Olgun and Reznik, 2010). In this study, we tried to find the relation between MMP-9 level in maternal serum and its expression in the fetomaternal membranes in cases of PROM at term and determine the histopathological changes of membranes with or without histological chorioamnionitis.…”
Section: Discussionmentioning
confidence: 99%